Makna Simbolik Stiker WhatsApp dan Normalisasi Humor Seksual di Era Generasi Zilenial - Lilian Putri, Deha D.; Putri, Nisrina Azka; Miyugi, Revio Xamanda; Ramba, Bernard Agung Barto; C.P, Adela Salsabila; Faishal, Abdurrahman (Institut Teknologi Sepuluh Nopember, 2025)
The rapid development of digital communication has increased the use of WhatsApp stickers as a dominant expressive medium, particularly among Generation Z. Stickers function not only as message enhancers but also as visual symbols carrying layered meanings and ideological values. Beneath their humorous and casual appearance, many stickers represent sexually connotative messages that may contribute to the normalization of symbolic sexual harassment in digital communication. This study aims to examine the representation and normalization of sexual harassment through WhatsApp stickers using a mixed approach that combines visual data analysis and contextual narrative interpretation. The research applies Roland Barthes’ semiotic framework, encompassing denotation, connotation, and myth. Data were collected through digital observation and documentation of selected stickers containing ambiguous meanings and sexual connotations, which were then interpreted within the context of contemporary digital culture. The findings indicate that stickers contribute to the construction of cultural myths that frame harassment as humor, thereby blurring the boundary between expression and violation. This study highlights the importance of visual communication literacy and critical awareness to prevent the normalization of sexual harassment in digital interactions.